EFFECT OF ELECTROSTATIC FIELD ON SOYBEAN SEED GERMINATION PARAMETARS - Mamlić (Miladinov), Zlatica J; Dozet, Gordana; Mamlić, Goran; Vasiljevic, Sanja; Đukić, Vojin; Katanski, Snežana; Bajagić, Marija (Journal on Processing and Energy in Agriculture, 2021)
The aim of this study was to examine the influence of electrostatic fields on seed vigor, mean rate of germination and coefficient of velocity of germination of five soybean genotypes. Testing was conducted at the Novi Sad Institute of Field and Vegetable Crops on the seeds of five soybean varieties: Sava, NS 2024, NS 1347, NS 3127, and NS Blackstar. The seeds were exposed to different values of direct current (DC) of the following voltage: 0 V (control), 3 V, 6 V and 9 V, to which the seeds were exposed for 0 min (control), 1 min and 3 min. After exposing the seeds to the electric field, the vigour index (VI), mean rate of germination (MGR) and coefficient of velocity of germination (CVG). The results show that the effect of the electrostatic field on seed vigour, mean rate of germination and coefficient of velocity of germination depends on the genotype, voltage and exposure time. The application of DC can be a suitable method for improving vigour index (VI), mean rate of germination (MGR) and coefficient of velocity of germination (CVG). In addition, the results indicate that it is necessary to adjust the DC treatment (voltage and duration of exposure of seeds) to a particular genotype, since inadequate treatments may deteriorate the quality of seeds.            Keywords: electrostatic field, vigor index, MGR, CVG, soybean
Keywords: electrostatic field, vigor index, MGR, CVG, soybean